PRINCIPLES OF ORGANIZATION OF BENCHMARKING SERVICE IN INDUSTRIAL ENTERPRISES (World Bulletin of Management and Law, 2023)
The implementation of benchmarking principles in industrial enterprises is the basis for creating an effective and promising economic strategy of the enterprise's production capacity and provides the stages for the implementation of the concept of strong competitiveness of the enterprise over its future competitors
Keywords: Industrial enterprises; strategy; management; benchmarking